Racial/ethnic differences in mental health and drug treatment among juvenile arrestees - Lopez, Vera (Journal of crime and justice, 2018)
The purpose of this study was to test for racial/ethnic differences in drug and mental health treatment-related perceptions and experiences among a sample of 377 juvenile arrestees. Bivariate analyses revealed that white juvenile arrestees reported receiving more past drug treatment and mental health messages than black, Latino, and ‘other’ juvenile arrestees. They were also more likely to perceive a need for mental health treatment than Latinos and other racial/ethnic minority arrestees. No racial/ethnic differences were found for past mental health treatment or perceive need for drug treatment. Multivariate analyses revealed that Latinos were less likely than white youth to perceive a need for mental health treatment; and other racial/ethnic minority youth were less likely than white youth to have ever received drug treatment even after controlling for demographic variables and risk factors. Practice implications are discussed.